An Optimized Immunoprecipitation Protocol for Assessing Protein-RNA Interactions In Vitro - Fuentes-Iglesias, Alejandro (STAR Protoc, 2020)
RNA-binding proteins are key regulators of cell identity and function, which underscores the need for unbiased and versatile protocols to identify and characterize novel protein-RNA interactions. Here, we describe a simple and cost-effective in vitro RNA immunoprecipitation (iv-RIP) method to assess the direct or indirect RNA-binding ability of any protein of interest. The versatility of this method relies on the adaptability of the immunoprecipitation conditions and the choice of the RNA, which exponentially broadens the range of potential applications. For complete details on the use and execution of this protocol, please refer to Guallar et al. (2020).